How Audience can be Engaged in VR Videos; A Critical Analysis of Sense of Presence, Enjoyment and Empathy - Naveed Ullah Hashmi; Dr. Noman Ansari; Dr. Wajid Zulqarnain (Journal of Management Practices, Humanities and Social Sciences, 2021)
Audience engagement has become a priority in the news industry. Journalists and news producers are adopting innovative ways of storytelling that can engage more and more audiences. For this, the producers and directors are using 360 VR technologies to boost audience engagement. However, there is scarce empirical evidence in underdeveloped countries on the relationship between 360 VR videos and audience engagement. Therefore, the study aimed to find out which element, including the sense of presence, enjoyment, and empathy, is more effective for audience engagement. For this experimental method was employed. Purposefully volunteers were recruited, and a 360 VR video taken from the website “The New York Times” named “The Displaced was shown to them. Their responses were collected on the pre-structured questionnaires. The findings showed that a sense of presence is very vital for audience engagement as the more audience “feel being there” in the 360 VR video, they will be engaged more similarly, the role of enjoyment and empathy is also very important in 360 VR videos. These three elements might be considered as the foundation of the 360 VR video industry. Therefore, the producers and the technology experts can get benefit from these results. It also contributes to the scarcity of 360 VR literature particularly. There is very limited empirical evidence on the relationship of sense of presence, enjoyment, and empathy with audience engagement in underdeveloped countries like Pakistan as this technology is in the very early stage.